2006
DOI: 10.3390/ijerph2006030046
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Impact of High Particulate Concentration on Peak Expiratory Flow Rate of Lungs of Sand Stone Quarry Workers

Abstract: This study was designed to assess the impact of high particulate concentration on peak expiratory flow rate of lungs of sand stone quarry workers. The workers were engaged in different types of activities such as drilling, loading and dressing. These different working conditions had different concentrations of RSPM, leading to different exposure levels in workers. It was found that exposure duration and exposure concentrations were the main factors responsible for damage to the respiratory tracts of the worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…Further, in addition to biologically weaker respiratory muscles, females are disadvantaged by multiple noxious exposures resulting in respiratory insult, such as indoor air pollution through the use of dirty fuels 17 (eg, cow dung, wood, grain husks, etc) yielding high quantities of air pol- lutants and exposure to dust-containing silica at the workplace that is also known to affect the respiratory system and pulmonary function. 18,19 The lower PEF in females in the present study can also be partly attributed to their significantly higher age as compared with the males.…”
Section: Discussionmentioning
confidence: 50%
“…Further, in addition to biologically weaker respiratory muscles, females are disadvantaged by multiple noxious exposures resulting in respiratory insult, such as indoor air pollution through the use of dirty fuels 17 (eg, cow dung, wood, grain husks, etc) yielding high quantities of air pol- lutants and exposure to dust-containing silica at the workplace that is also known to affect the respiratory system and pulmonary function. 18,19 The lower PEF in females in the present study can also be partly attributed to their significantly higher age as compared with the males.…”
Section: Discussionmentioning
confidence: 50%
“…These miners are often exposed to the respirable silica with the potential for the development of increased rates of malignant and non-malignant respiratory diseases including obstructive lung disease lung function impairment, silicosis and lung cancer. [6 32 33] In this survey of NJ quarry/mine workers, we not only found a high prevalence of cigarette smoking but also of other tobacco product use including e-cigarettes. E-cigarette use is rapidly increasing among US adults.…”
Section: Discussionmentioning
confidence: 76%
“…In Pakistan, Leghari et al [6] described high prevalences of respiratory symptoms among stone-crushing workers. In India, studies among quartz stone grinders by Tiwari et al [30][31][32][33] and among sandstone crushers by Singh et al [34,35] and Rajavel et al [36] identified silicosis, silico-tuberculosis, and respiratory functional impairment in a high proportion of exposed workers, even at a young age. In Nigeria, Nwibo et al [37] studied 403 male and female stone quarrying workers [mean age 30 years (SD 9 years)] by means of a questionnaire, spirometry, and chest radiography, and they concluded (without having a control group) that stone quarrying may increase the risk of respiratory symptoms and impaired lung function.…”
Section: Discussionmentioning
confidence: 99%